Can participation promote psychological ownership of a shared resource? An intervention study of community-based safe water infrastructure. (June 2022) - Ambuehl, Benjamin; Kunwar, Bal Mukunda; Schertenleib, Ariane; Marks, Sara J.; Inauen, Jennifer
Abstract: Previous research suggests that community-based participation, a process through which beneficiaries can actively influence and define the direction and execution of development programs, can promote long-term uptake, use, and management of shared resources, such as community-based safe water infrastructure. However, results are heterogeneous. Psychological ownership theory and initial evidence suggests that participation promotes positive outcomes for shared resources by fostering sense of ownership through three routes: having control, intimate knowledge, and investing the self. This study used community-based safe water infrastructure as an example to investigate how various forms of participation affect acceptance, use, and functionality of a shared resource and whether this effect is mediated by psychological ownership. We conducted a nonrandomized cluster-based controlled trial with pre–post intervention assessment (N = 369) in 33 villages in rural Nepal, where safe water infrastructure is shared. Participatory intervention activities (e.g., influence in decision-making, contributing materials and labour) favourably affected self-reported outcomes and use of the water supply infrastructure but not observed functionality or drinking water quality. In conclusion, this study supports the assumption that participation can foster psychological ownership, which in turn can support successful management of a shared resource. Highlights: Participation leads to increased acceptance, use, and improved management of community-based safe water infrastructure. Psychological ownership partially mediates the effects of some forms of participation on some outcomes. Psychological ownership is an additional factor that supports successful management of shared resources.